Perception And Practices of Healthy Lifestyle in Late Adolescence and Its Impact on Body Mass Index - Hala M Elsabagh; Fatma E Soliman; Lulah A Hassan (National Journal of Community Medicine, 2016)
Background: Adolescence coincides with major changes that affect the determinants of adult health. Many adult health conditions are related to factors that develop during adolescence.